Intracellular distribution of nontargeted quantum dots after natural uptake and microinjection - Damalakiene, Leona (Dove Medical Press, 2013)
BACKGROUND: The purpose of this study was to elucidate the mechanism of natural uptake of nonfunctionalized quantum dots in comparison with microinjected quantum dots by focusing on their time-dependent accumulation and intracellular localization in different cell lines. METHODS: The accumulation dynamics of nontargeted CdSe/ZnS carboxyl-coated quantum dots (emission peak 625 nm) was analyzed in NIH3T3, MCF-7, and HepG2 cells by applying the methods of confocal and steady-state fluorescence spectroscopy. Intracellular colocalization of the quantum dots was investigated by staining with Lysotracker(®). RESULTS: The uptake of quantum dots into cells was dramatically reduced at a low temperature (4°C), indicating that the process is energy-dependent. The uptake kinetics and imaging of intracellular localization of quantum dots revealed three accumulation stages of carboxyl-coated quantum dots at 37°C, ie, a plateau stage, growth stage, and a saturation stage, which comprised four morphological phases: adherence to the cell membrane; formation of granulated clusters spread throughout the cytoplasm; localization of granulated clusters in the perinuclear region; and formation of multivesicular body-like structures and their redistribution in the cytoplasm. Diverse quantum dots containing intracellular vesicles in the range of approximately 0.5–8 μm in diameter were observed in the cytoplasm, but none were found in the nucleus. Vesicles containing quantum dots formed multivesicular body-like structures in NIH3T3 cells after 24 hours of incubation, which were Lysotracker-negative in serum-free medium and Lysotracker-positive in complete medium. The microinjected quantum dots remained uniformly distributed in the cytosol for at least 24 hours. CONCLUSION: Natural uptake of quantum dots in cells occurs through three accumulation stages via a mechanism requiring energy. The sharp contrast of the intracellular distribution after microinjection of quantum dots in comparison with incubation as well as the limited transfer of quantum dots from vesicles into the cytosol and vice versa support the endocytotic origin of the natural uptake of quantum dots. Quantum dots with proteins adsorbed from the culture medium had a different fate in the final stage of accumulation from that of the protein-free quantum dots, implying different internalization pathways.